Giant radiative thermal rectification using an intrinsic semiconductor film. (March 2022) - Li, Qizhang; Chen, Qun; Song, Bai
Abstract: Rectification of heat flow via a thermal diode is not only of fundamental interest, but can also enable a range of novel applications in thermal management and energy conversion. However, despite decades of extensive research, large rectification ratios of practical importance have yet to be demonstrated. Here, we theoretically achieve giant rectification ratios (3 to almost 5 orders of magnitude) by leveraging near-field radiative thermal transport between two parallel planes. Guided by a rational design approach centering on the electromagnetic local density of states (LDOS), we employ a thin film of an intrinsic semiconductor—such as silicon—as one terminal of our radiative thermal diodes, which provides the necessary nonlinearity and a substantial LDOS contrast as the temperature bias is flipped. For the other terminal, we explore two kinds of materials which either serve as a narrowband or a broadband filter, both capable of converting the large LDOS contrast into giant thermal rectification. We further consider representative multilayer configurations in order to block backside radiation and improve mechanical stability. All the designs are expected to perform well over a wide range of film thicknesses, gap sizes, and temperatures. Our work offers an opportunity for realizing thermal diodes with unprecedented rectification ratios. Graphical abstract: Image 1 Highlights: Radiative thermal diodes of ultrahigh rectification are proposed by leveraging near-field transport. A rational design approach centering on the electromagnetic local density of states is demonstrated. Key to our diodes is a thin film of intrinsic semiconductor such as silicon.